PERANCANGAN SISTEM PENJUALAN BERBASIS WEB - Dadi Rosadi; Nuri Nuryani Subarya (Jurnal Computech & Bisnis (e-Journal), 2018)
The process of ordering goods takes a long time, by submitting an order form that will go through several parts. As for some of the possibilities received in this order, the items ordered do not exist, or the forms that have been made are lost, or when the goods received are not in accordance with the order.The use of information technology is very helpful in providing information that is quite effective. Internet technology is an effective medium of information in disseminating information. The internet can be accessed anytime, anyone and anywhere as long as there is a connection. Internet technology has a considerable impact on the business world, this makes it easier for people in commerce to be more practical, cost-effective and time efficient. With the advancement of technology today, it is easier for people to transact without having to meet face to face with the seller. Utilizing these advantages, today some people make transactions through the internet.With this system the buyer will know in advance the information about the goods available in the warehouse, data archiving can be arranged neatly, so as to facilitate data search, facilitate the warehouse admin in managing buying and selling transactions, he will receive the purchase form more quickly, so buyers will get a response/information quickly, accurately and effectively directly from the warehouse of goodsKeywords: Information Systems, Sales, InventoryDOI 10.5281/zenodo.3373775